Variation in community structure and biomass production of shrub and herb layer in agroforestry systems in Himachal Pradesh -Acase study - Thakur, N.S.; Gupta, N.K.; Gupta, B. (Indian Journal of Agroforestry, 2020)
Biomass production of under storey vegetation (shrub and herb layer) was investigated in Kuthar Forest range (village Krishangarh), District Solan of Himachal Pradesh, under three natural agroforestry systems viz; Agrisilviculture (AS), pastoral-silviculture (PS) and pastoral-silvihorticulture (PSH). Shrub layer was dominated by Murraya koenigii in all the three land uses, with maximum biomass production under PS (6852.04 kg/ha). PS system provided maximum biomassÂ (11771.84 kg/ha) from seven shrub species encountered in this system. Gross returns were also higher from M. koenigii under all the systems. Herbaceous layer was dominated by Chrysopogon montanus because of higher density and basal area per hectare. Maximum herb density was recorded under PS system, hence the total biomass (4865.99 kg/ha). Variation in biomass production of under storey vegetation under three systems may be attributed to the nature of the system, management practices and the use to which system is being put in.